Historical, philosophical, and legal foundations of education - Lacuesta, Manuel G.; San mateo, Rosalinda A.; Tangco, Maura G.; Eslao, Rufino O. (Philippines : Philippine Association for Teacher Education and Katha Publishing Co., Inc., 1986)
The major purpose in writing this book was to answer the demands for teaching materials in the new course for bachelor of elementary education. This Textbook does not simply present information, it is also designed to teach.
Part I. Historical Foundations of education -- Part II. Philosophical foundations of education -- Part III. The Philippines educational systems: its legal bases, administrative organization, and financing.
Includes bibliographical references.
Keywords: EDUCATION HISTORY; EDUCATION PHILOSOPHY